Supervenience: Its logic and its inferential role in classical genetics - Leuridan, Bert (Logique et analyse, 2007)
Supervenience is mostly conceived of as a purely philosophical concept. Nevertheless, I will argue, it played an important and very fruitful inferential role in classical genetics. Gregor Mendel assumed that phenotypic traits supervene on underlying factors, and this assumption allowed him to successfully predict and explain the phenotypical regularities he had experimentally discovered. Therefore it is interesting to explicate how we reason about supervenience relations. I will tackle the following two questions. Firstly, can a reliable method (a logic) be found for inferring supervenience claims from data? Secondly, can a reliable method (a logic) be found to empirically test supervenience claims? I will answer these questions within the framework of the adaptive logics programme.